The importance of the electoral rule: Evidence from Italy - Massimo Bordignon; Andrea Monticini (Center for Economic Studies and ifo Institute (CESifo), 2011)
We employ bootstrap methods (Efron (1979)) to test the effect of an important electoral reform implemented in Italy from 1993 to 2001, that moved the system for electing the Par-liament from purely proportional to plurality rule (for 75% of the seats). We do not find any effect on either the number of parties or the stability of governments (the two main objectives of the reform) that remained unchanged at their pre-reform level.
Keywords: H00; 330; electoral system; plurality rule; Duverger's law; bootstrap; Wahlsystem; Reform; Wirkungsanalyse; Politische Partei; Pluralismus; Politische Stabilität; Italien